In Vitro Induced Resistance of Fusarium Wilt Disease (Fusarium oxysporum f.sp. cepae) by Salicylic Acid in Shallot CV ‘Bima Brebes’ - Khusnul Khotimah; Endang Sulistyaningsih; Arif Wibowo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Fusarium wilt caused by Fusarium oxysporum f.sp.cepae (Foc) is one of the most important diseases of onion in Indonesia. Induced resistance was one of the effective techniques to acquire resistance to fusarium wilt in shallot. Salicylic acid (SA) had been inferred to be in endogenous signal in the systemic acquired resistance response of plants. This research aimed to study the effect of exogenously added SA to resistance in shallot callus cv ‘Bima Brebes’ to fusarium wilt disease in vitro; and to determine the effective concentration of SA to induce resistance. A group of shallot callus was grown in MS medium containing varying SA concentration (0, 15, 20 and 25 ppm) in vitro for 2 weeks. Then, the callus were treated with toxin of Fusarium oxysporum, namely fusaric acid, to have observe the resistance response. In vitro selection was done twice in different fusaric acid concentration. Application of exogenous SA at all concentration did not suppres time of appearance of disease symptom yet. Toxic symptom in the callus was shown by the browning or blackening (off) of callus. Salicylic acid at concentration of 20 ppm effectively reduced the toxic symptom up to 16.66% and supported callus regeneration better than the concentration of 15 ppm and 25 ppm. The number of resistant callus regenerated was 66.67% at pretreatment of 20 ppm of SA.